Effects of Cell-Based Therapy for Treating Tympanic Membrane Perforations in Mice. (June 2016) - Goncalves, Stefania; Bas, Esperanza; Goldstein, Bradley J.; Angeli, Simon
Objective: To investigate the effectiveness of scaffold-embedded mesenchymal stem cells (MSCs) as a topical treatment for healing tympanic membrane perforations (TMPs) in a mouse model. Study Design: Prospective animal study. Setting: Experimental. Subjects and Methods: In vitro: under sterile conditions, porcine-derived (Gelita-Spon [GS]), hyaluronate-derived (EpiDisc [ED]), and polyvinyl alcohol (PVA) scaffolds were cut into small pieces and cocultured with murine bone marrow–derived MSCs (BM-MSCs) expressing green fluorescent protein (GFP) for 72 hours. The cultures were either analyzed by confocal microscopy or used for subsequent in vivo experiments. In vivo: 26 mice were divided into 3 groups (ie, control [n = 9], GS [n = 8], ED [n = 9]). Under general anesthesia, TMPs of equal sizes were performed bilaterally using a sterile 27-gauge needle under a surgical microscope. The BM-MSCs embedded within GS or ED scaffolds were soaked in phosphate-buffered saline and then topically applied on right TMPs, and scaffolds alone were applied on left TMPs 6 to 8 hours after injury. Control mice did not receive treatment. On day 7, animals were euthanized and bullae were harvested for histological analysis. Results: In vitro: BM-MSCs grew well on both GS ( P = .0012) and ED ( P = .0001) scaffolds compared with PVA. In vivo: 100% of untreated (control) TMPs remained open after 7 days. Animals treated with MSC-embedded ED scaffolds had a higher percentage of TMP closure ( P = .016) and a thicker neotympanum ( P = .0033) than control animals. The experimentally applied BM-MSCs engrafted and differentiated into epithelial cells suggested by the colocalized expression of cytokeratin-19 and GFP. Conclusions: The topical application of bone marrow–derived MSCs enhances the healing of TMPs in this animal model and is a promising alternative to tympanoplasty.